Numerical evaluation of the post-earthquake fire resistance of CFRP-strengthened reinforced concrete joints based on experimental observations. Issue 2 (7th February 2016) - Behnam, Behrouz; Ronagh, Hamid Reza; Lim, Pang Jen
Abstract : This article describes experimental and numerical studies on the structural resistance of two reinforced concrete beam-column joints. While both specimens are of similar configurations as for geometry, amount and type of steel reinforcement and concrete strength, the second is strengthened by means of carbon fibre-reinforced polymer (CFRP) at the vicinity of the joint in order to relocate the plastic hinge away from the column extremity towards the beam. Both specimens are subjected to a cyclic load followed by a generalised exponential fire curve, which implicitly represents a post-earthquake fire (PEF). The PEF resistance of the specimens subjected to various damage levels such as immediate occupancy (IO), life safety (LS) and collapse prevention (CP) is then evaluated based on finite element analysis. The results show that while the fire resistances of the original specimen subjected to LS and CP damage levels are about 32 and 15 min, respectively, they increase in the CFRP-strengthened specimen to about 43 and 23 min, respectively. This represents a 25% increase at LS level and a 35% increase at CP level.